1996
DOI: 10.1021/ic950832b
|View full text |Cite
|
Sign up to set email alerts
|

Protonation Equilibria of Mononuclear Vanadate:  Thermodynamic Evidence for the Expansion of the Coordination Number in VO2+

Abstract: A spectrophotometric investigation of the protonation of HVO(4)(2-) has been conducted at vanadium(V) concentrations low enough (5 x 10(-5) mol dm(-3)) to prevent the formation of polynuclear ions. Equilibrium constants as well as enthalpy and entropy changes for the formation of H(2)VO(4)(-) and VO(2)(+) have been determined in ionic medium: 1.0 mol dm(-3) NaCl and NaClO(4), respectively. The percentage concentration of the neutral species, H(3)VO(4), is so low (apparently <1%) that the protonation of H(2)VO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
(21 reference statements)
1
27
1
Order By: Relevance
“…This neutral molecule H 3 VO 4 (or more precisely VO(OH) 3 ) is well known to exist at room temperature and at low pH (∼3.5) [14,17]. Recently, Sadoc et al [18] reported that the hydrated VO 2 + molecule is prone to deprotonation at high temperatures (500 K), resulting in the formation of VO(OH) 2 (H 2 O) 2 + and subsequently the neutral H 3 VO 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This neutral molecule H 3 VO 4 (or more precisely VO(OH) 3 ) is well known to exist at room temperature and at low pH (∼3.5) [14,17]. Recently, Sadoc et al [18] reported that the hydrated VO 2 + molecule is prone to deprotonation at high temperatures (500 K), resulting in the formation of VO(OH) 2 (H 2 O) 2 + and subsequently the neutral H 3 VO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…This VO 2 + species reportedly exists in its hydrated form with a six-coordinated octahedral structure in which two oxygen atoms are coordinated in cis-configuration along with four complexed water molecules (i.e. [VO 2 (H 2 O) 4 ] + ) [14]. However, our DFT based geometry optimization revealed that this octahedral vanadate ion structure is not energetically favorable and a slightly more stable structure is formed by repelling a water molecule located at trans position to the vanadyl oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…In vanadium(V) complexes, the (HVO 4 ) 2-group is well known and present in numerous structures [22][23][24]. However, until now a (HVO 4 ) 2-group was not found among purely inorganic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Thermodynamic data for the appropriate protonation equilibria have been taken as evidence for a corresponding expansion of the coordination number about vanadium [45] (that is, from four in 1 to six). Indeed, a minimum can be located for [VO 2 (OH 2 ) 4 ] with a distorted octahedral coordination sphere around the metal (2 a, Figure 5).…”
Section: Vo 2 (Aq)mentioning
confidence: 99%